Nursing process as a method of work - Szewczyk, Maria T.; Cierzniakowska, Katarzyna; Stodolska, Alina; Cwajda, Justyna; Górna, Violetta (Przewodnik Lekarza/Guide for GPs, 2005)
Conception of nursing process was evolved in the 50’ of XX century in USA. In Poland nursing process as a method of work is used in many hospitals and outpatient clinics. It is a dynamic and universal method of nursing which can be used in every situation. This method leads to cyclic identification and solving patients’ problems. This article discusses theoretical principles of nursing and special documentation.